The Dark Side of Connectivity: A Socio-Ethical Exploration of Internet Fraud and Nigerian Youth - Wariboko, Onyinyechi Priscilla Christian; Nwanyanwu, Friday Chimene (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Internet fraud, popularly known as ‘yahoo-yahoo’ in the Nigerian parlance, reverberates across the Nigerian state and keeps gaining approval as somewhat permissible as days go by. Humongous media reports abound as well as other surreptitious or conspicuous activities of internet fraudsters in Nigeria. A great deal of Nigerian youths have embraced it and has jettisoned hard work, process, building from the scratch, integrity, compassion and pay little or no attention to education. This state of affairs has social and ethical implications for Nigeria as a state. With insights drawn from Robert Merton’s structural strain theory and Aristotle’s virtue ethics, this paper qualitatively examines the spate of indiscreet deals by criminally minded Nigerian youth and particularly mirrors its social and ethical implications. Data is gathered through interviews, observations and literal readings. Findings show that internet fraud, which is eating deep into the fabric of Nigeria has exacerbated the get-rich-quick syndrome, disrupted the smooth running of the nation and holds dire socio-ethical consequences for the future of the nation. This paper recommends that the government, family unit, as well as religious organizations must play salient roles in sensitizing, educating, guiding and sanctioning internet criminals for the good of society. This research contributes to existing knowledge by exploring the phenomenon of internet fraud in Nigeria through the lenses of sociology and ethics, yielding recommendations that stem from these disciplines to combat the problem.